EPIDEMIOLOGICAL STUDIES, CLINICAL EPIDEMIOLOGY AND EVIDENCE-BASED MEDICINE - N. I. Briko; V. I. Pokrovsky (Сеченовский вестник, 2010)
Interrelations between clinical epidemiology and evidence-based medicine are discussed. Demonstrated that epidemiological studies are the methodological basis of clinical epidemiology and evidence-based medicine. Areas of application of evidence-based medicine in clinical and social medicine, as well as in healthcare management and medical education are shown. The sources of the information system accessible evidence-based medicine are given.